2017
DOI: 10.1021/acsami.7b01702
|View full text |Cite
|
Sign up to set email alerts
|

Roles of 3-Ethylrhodanine in Attaining Highly Ordered Crystal Arrays of Ambipolar Diketopyrrolopyrrole Oligomers

Abstract: Until now, only limited DPP oligomers delivered ambipolar semiconductor characteristics. To develop a facile strategy of preparing ambipolar mono-DPP oligomers, two dithienyl diketopyrrolopyrrole (DPPT) based-conjugated molecules, DPPT-RD and DPPT-DCV, which contain 3-ethylrhodanine (RD) and dicyano-2-vinyl (DCV) end substituents were synthesized. The influences of the -RD end substituents on the molecular properties, solid-state morphology, and OFET performances of the DPPT oligomer were investigated. The UV–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 54 publications
0
26
0
Order By: Relevance
“…This is a first green strategy toward the synthesis of DPPRD. Compared with previous reported literature, the improved synthetic method shows the following advantages: an hypotoxic solvent of dichloromethane replacing hazardous and carcinogenic solvents of chloroform and piperidine and no need of heating/reflux and nitrogen/argon protection during the reaction process. According to the mild synthesis conditions described above, this improved synthetic method with environmentally friendly features has potential to the practical application in industrial production because it is expected to reduce energy consumption and simplify the operation process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a first green strategy toward the synthesis of DPPRD. Compared with previous reported literature, the improved synthetic method shows the following advantages: an hypotoxic solvent of dichloromethane replacing hazardous and carcinogenic solvents of chloroform and piperidine and no need of heating/reflux and nitrogen/argon protection during the reaction process. According to the mild synthesis conditions described above, this improved synthetic method with environmentally friendly features has potential to the practical application in industrial production because it is expected to reduce energy consumption and simplify the operation process.…”
Section: Resultsmentioning
confidence: 99%
“…Diketopyrrolopyrroles (DPPs) are a star-conjugated acceptor system which possesses favorable properties of strong light absorption and high photochemical stability. , Chen et al reported that introducing the 3-ethylrhodanine (RD) units in the terminal position of DPP could improve solar light absorption . Very recently, an ambipolar optoelectronic molecule, containing the strong electron-withdrawing units of DPP and 3-ethylrhodanine (RD), has been designed and explored in the organic solar cells. However, there are few examples of using π-conjugated organic semiconducting molecules as photocatalysts for the degradation of organic pollutants under visible light irradiation. Recently, the composited organic photocatalyst obtained through π–π interactions of 7,7,8,8-tetracyanoquinodimethane and perylene tetracarboxylic diimide was reported to show high efficiency for the visible light-irradiated degradation of phenol .…”
Section: Introductionmentioning
confidence: 99%
“…The performance of these transistors was very stable and highly reproducible in air. These results suggest that the electrical performance of a compound, especially one exhibiting polymorphism, can be improved by changing the crystallization factors to reach the desired molecular packings; this approach provides a novel means of developing new electrical materials …”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that the electrical performance of a compound, especially one exhib iting polymorphism, can be improved by changing the crystal lization factors to reach the desired molecular packings; this approach provides a novel means of developing new electrical materials. [32][33][34] In conclusion, we have synthesized a polymorphous com pound, TCBR, for use as a typical donor-acceptor conjugated molecule. We obtained four different single crystals based on the cis and trans isomeric forms of this compound.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
“…The past decades have witnessed the significant progresses of organic and polymeric semiconductors. [1][2][3][4][5] Various conjugated frameworks, such as diketopyrrolopyrrole (DPP), [6][7][8][9][10][11][12][13][14][15] naphthodithiophenediimide (NDTI), [16][17][18][19][20][21][22][23] benzodifurandione-based oligo(p-phenylene vinylene) (BDOPV) [24] and isoindigo, [25][26][27][28] have been explored to construct the conjugated molecules and polymers for semiconductors of high charge mobilities. For instance, the electron deficiency,p lanar conjugated structure and easyf unctionalizatione nableD PP as av ersatile building block for organic and polymerics emiconductors.…”
Section: Introductionmentioning
confidence: 99%